Analisis Hubungan Intensitas Pencahayaan dan Kelelahan Mata terhadap Produktivitas Kerja pada Pekerja Konveksi Tahun 2022 - Zulham Dwi Pratikto; Ekaterina Setyawati; Djamal Thaib (Syntax Corporation, 2023)
The garment industry must have three main assets: fabrics, sewing machines, and sewing machine operators. Because the amount of finished garments produced is dependent on the sewing machine operator, he or she is the most important person. However, in reality, it is known that this section has a lighting intensity below the average compared to the applicable government policy, so it is found that it causes several symptoms of complaints of eye fatigue, which have an impact on the rise and fall of the level of work productivity of workers. This research method is explanatory, with data collected via questionnaires and interviews, as well as total sampling techniques. Respondents are employees of Dodik Garment and CV. Arga Garment. The analysis technique used is the Pearson correlation coefficient, the coefficient of determination, and the significance test, which were tested using SPSS for Windows version 27.0. The results of this study indicate that the lighting intensity is below the minimum standard. Most workers complain of eye fatigue, which manifests as symptoms such as red eyes, drowsiness, and headaches. All independent variables, namely lighting intensity (X1) and eye fatigue (X2), simultaneously (simultaneously) or individually (partially) affect the dependent variable, work productivity (Y). Some suggestions that can be given are the need for supervision from related government agencies, carrying out routine maintenance, redesigning room layouts to maximize lighting distribution, conducting periodic eye health checks, and making regulations and Standard Operating Procedures (SOP) to minimize the risk of eye fatigue complaints